Infrastructure and city competitiveness in India - Somik V. Lall; Hyoung Gun Wang; Uwe Deichmann (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Do local improvements in infrastructure provision improve city competitiveness? What public finance mechanisms stimulate local infrastructure supply? And how do local efforts compare with national decisions of placing inter-regional trunk infrastructure? In this paper, we examine how the combination of local and national infrastructure supply improve city competitiveness, measured as the city's share of national private investment. For the empirical analysis, we collect city-level data for India, and link private investment decisions to infrastructure provision. We find that a city's proximity to international ports and highways connecting large domestic markets has the largest effect on its attractiveness for private investment. In comparison, the supply of local infrastructure services - such as municipal roads, street lighting, water supply, and drainage - enhance competitiveness, but their impacts are much smaller. Thus, while local efforts are important for competitiveness, they are less likely to be successful in cities distant from the country's main trunk infrastructure. In terms of financing local infrastructure, we find that a city's ability to raise its own source revenues by means of local taxes and user fees increases infrastructure supply, whereas as inter governmental transfers do not have statistically significant effects.
Keywords: O18; N95; R51; 330; urbanization; cities; India; infrastructure